“Without bloodshed: the Independence of Brazil in Latin American textbooks (Argentina, Ecuador, Mexico, and Venezuela) (Revista de Estudios Brasileños, 2023)
The present article problematizes the history of Brazilian Independence from the Latin-American textbooks’ point of view. I analyzed seventeen books from Argentina, Ecuador, Mexico, and Venezuela. The main goal is to figure out in what way a still dominant version of Brazilian Independence is a peaceful rupture. I could see a conservative predominance and little relevance in the corpus of these analyzed textbooks. A question remains: why is Brazilian Independence’s history not central in these materials? An interrogation that seeks to prompt new investigations about this theme.